Study on anti-cracking properties of biopolymer-improved clay on open pit mine slopes - Xiang QI; Wei ZHOU; Zhile WANG; Rui LI; Ya TIAN; Lixiao TU; Zhiyuan ZHANG; Zhilong DONG; Huxiong YANG (Meitan kexue jishu, 2025)
Slope stability is of great significance in open pit mines and other projects, while the formation and expansion of slope cracks under the action of rainwater may lead to slope instability and damage, and the introduction of biopolymers may have a significant effect on the drying and cracking properties of clay slopes. To investigate the effectiveness of biopolymers in improving the dry shrinkage cracking performance of clay slopes, the clay from the Xiaolongtan open pit coal mine was selected as the research object, and the biopolymers Artemisia sphaerocephala Krasch gum(ASKG) and Xanthan gum (XG) were introduced for the modification treatment. To evaluate the anti-cracking effect and durability of different dosages of biopolymers, a series of dry and wet cycle tests were carried out the change of water content was recorded, and the indexes such as fracture rate and probability entropy were quantitatively analyzed through PCAS software processing. The results showed that the incorporation of biopolymers would advance the time of fracture appearance and affect the final water content of the specimen, in which 1% dosing of ASKG could enhance the final water-holding capacity of the clay body by 53.5%; the incorporation of biopolymers significantly reduced the fracture rate of the clay, but the effect on the probabilistic entropy was not obvious, and the 1% dosing of ASKG and 1% dosing of XG in the first dry and wet cycle could reduce the fracture rate of the clay by 11.83% and 16.39%, respectively. 11.83% and 16.39%, with the increase in the number of wet and dry cycles, the cracking resistance of ASKG specimens gradually decreases, while XG shows some durability. Based on the experimental results, XRD and SEM techniques were used to discuss the mechanism of biopolymers affecting the cracking resistance of the clay body, and it was found that the incorporation of biopolymers did not change the clay components, but the biopolymers were able to form a stable association with clay minerals through electrostatic bonding and hydrogen bonding, and at the same time, they formed a gel by mixing with water, which encapsulated and connected soil particles at the microscopic level and filled up the pore space, effectively resisting the cracking resistance caused by water loss of clay body. It effectively resists the cracking tension caused by the water loss of clay. To resist the tension of clay water loss and cracking. This study comprehensively analyzes the characteristics of the two biopolymers, ASKG and XG, in improving the cracking performance of clay, which provides a reference for the management of clay slope cracking in open-pit mines.